Effects of pH and water turbulence on the growth of harmful algae pyrodintum bahamense var. compressum - Muhamad Shaleh, Sitti Raehanah; Edrews, Dianecia; Mohammad Noor, Normawaty; Anton, Ann (2010)
Pyrodinium, a red tide causing dinoflagellates are often related to toxicity cases particularly paralytic shellfish poisoning (PSP). Study on the effects of specific parameter on the growth it fy*ai"iin is essential to determine the potential factors r-esponsible for thek occurrences. The effects or iH ana turbulence on the growth of Pyrodinium bahamense var. compressun was conducted in laboratory under controlled conditions. P bahamense was cultured in nine different pH levels under two conditions; with and without water turbulence. The experiments were conducted under constant light intensity 100 pmolm-2s{ at 25"C with photoperiod of 12h'light:12 h dark bycle. Cells were incubated for two weeks'and **pri"gr *";;;;" for growth deterrnination every day at interval. This study shows thatP bahamenseattained the highest cell density (616 cells mT:t; when grown at pH 8-5 without water motion. However, in the presence of Ilow water turbulence or water motion, the cell density is relatively low (128 cells ml,-r) at pH 8.5. These different outcomes might be due to the growth inhibitory effect of water motion to P bahameise. Celldensities of p. bahamensewere also found significantly lower at acidic conditions (< 7.0) and at higher pH (> 9.0)